Cancer risks among the users of ergot-derived dopamine agonists for Parkinson's disease, a nationwide population-based survey. Issue 1 (January 2015) - Wang, Vinchi; Chao, Tzu-Hao; Hsieh, Chung-Chih; Lin, Che-Chen; Kao, Chia-Hung
Abstract: Background: Factors of cancer occurrence among Parkinson disease patients are still not well known, although genetic predilection has been investigated. The aim of this study is to evaluate the medication effect of dopamine agonists of Parkinson disease on incidence of cancers from the Taiwan National Health Insurance Research Database. Methods: We conducted a population-based nested case–control study by using the resources of the Taiwanese National Health Insurance from 1996 to 2000 and analyzed the prevalence of cancer among patients with Parkinson disease. A nested analysis was then implemented among those patients with both Parkinson disease and cancer, focusing separately on the use of ergot- and nonergot-derived-dopamine agonists. Results: We reviewed 6211 patients with Parkinson's disease and found 329 patients with cancer. The ergot-derived dopamine agonists users were associated with an increased odds ratio for cancer, compared with nonergot-derived dopamine agonist users, with an adjusted odds ratio of 2.16 (95% confidence interval, 1.55–2.99). Among all the cancer types, we observed the higher occurrence of liver cancer among the ergot-derived dopamine agonist users. Conclusion: The association of ergot-derived-dopamine agonist use and cancers, especially the liver cancers, has provided us the information to further understand the drug–cancer interaction. We hope this result would prompt further investigations on the risk and benefit of the dopamine agonists use among the Parkinson's disease patients. Highlights: Ergot-derived dopamine agonists were associated with an increased risk of cancers. The higher occurrence of liver cancer in the ergot-derived dopamine agonist users. Further investigations on the risk and benefit of the dopamine agonists.